Community action: A neglected site of innovation for sustainable development? - Gill Seyfang; Adrian Smith (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
Innovation and community action are two important areas of research and policy for sustainable development. Yet these two spheres of activity have not hitherto been linked. This paper builds a case for considering community action as a neglected, but potentially important, site of innovative activity. In so doing, the paper bridges a divide in a way that offers a novel theoretical approach to the study of community-level action for sustainability. It discusses some of the opportunities presented by grassroots innovation, and some of the challenges confronting activity at this level. By conceiving of the grassroots as a niche site for innovation a new agenda for community-level sustainable development research and policy support emerges.
Keywords: 330; community action; innovation; Social economy; sustainable consumption; Sustainable Development